Contrasting Two Verbal Fluency Scoring Systems Using the Rasch Rating Scale Model - Prieto, Gerardo (2018)
Objective: Two scoring systems for a verbal fluency test were compared using the Rasch Rating Scale Model. Method: The analysis was carried out on 289 participants, 92 of  whom had had a Parkinson’s disease  diagnosis.  Scores  were  calculated  with  two  different  category  systems:  a  conventional  procedure  and  a  percentile-based  one.  Results:  The  percentile-based  Rasch  scores  produce  adequate  categories  and  reliable  measures,  while  the  correlation  with  the  Mini  Mental  State  Examination  evinces  concurrent  validity. After statistically controlling for age, percentile-based Rasch measures discriminated between both groups,  demonstrating  predictive  validity.  Conclusions:  The  analysis  of   the  two  procedures  allows  for  the  recommendation of  the use of  percentile-based categories,